Using mesoporous thin films as nano-micro-fluidic tools - Berli, Claudio Luis Alberto (2022)
Achieving active control on small amounts of liquids represents a substantial challenge in both scientific and engineering aspects. Imbibition of fluids in bodies with nanoscale dimensions enables the spontaneous propelling of nano-flows because of the powerful capillarity at small-length scales. Peculiarities of nanopore imbibition at the thin film level lead to distinctive capillary transport phenomena of fluids across the nanopore matrix. This particular imbibition also impacts on the behavior of the in-contact liquid micro-volumes. These both features add versatile alternatives to the high interest in the management of femtolitre to microlitres amounts of liquids. Herein, we show a brief discussion-outlook based on recent advances in the design of versatile tools to attain programmable nano/microfluidics using mesoporous thin film platforms.